Just Transition to Zero Waste Cities: A Key Strategy to Deliver the Paris Agreement - Zaman, Atiq; Grate, Froilan; Herrera, Rachel Anne; Heyman, George; Rocha, Anna le; Myronova, Iryne; Swannell, Richard (UNFCCC, 2022)
Increasing GHG emissions in cities (from 60% in 2000 to 67% in 2015), can be greatly reduced through just transition strategies toward circular and zero-waste local economies.